Stakeholder engagement in strategic planning for academic library (case study at Perpustakaan Tengku Anis, Machang, UiTM Kelantan Branch) / Koko Srimulyo and Syahril Ulya - Srimulyo, Koko; Ulya, Syahril (Faculty of Information Management, 2023)
Strategic planning is a management approach used by various institutions and libraries are no exception. Academic libraries optimise their activities through strategic planning while helping to realise the strategic plan of the main institution, the university. Staff involvement is one of the important elements in a series of strategic planning processes. This article was prepared to find out the staff involvement process carried out by Perpustakaan Tengku Anis (PTA) in strategic planning. The research approach is a case study with data collection methods of literature review and interviews. The results showed that PTA has involved staff in the strategic planning process with grassroots strategic planning approach through a dialogic approach with the implementation of deliberations or focus group studies. The involvement of staff in the strategic planning process has been able to provide opportunities for all staff to be involved and contribute in realising the strategic plan with full awareness and shared responsibility